Plasma levels of dioxins, furans, non-ortho-PCBs, and TEQs in the Seveso population 17 years after the accident / Livelli plasmatici di diossine, furani, non-orto-PCB e TEQ nella popolazione di Seveso 17 anni dopo l’incidente - Consonni, D.; Sindaco, R.; Agnello, et al., L. (La Medicina del Lavoro, 2012)
Background: The Seveso accident (Italy) in 1976 caused the contamination of a large population by 2,3,7,8-tetrachlorodibenzo-para-dioxin (2,3,7,8-TCDD). The contaminated territory was divided into three zones: A (very high contamination), B (high contamination), and R (low contamination). We report here the plasma concentrations of seven polychlorinated dibenzo-para-dioxins (PCDDs), 10 polychlorinated dibenzofurans (PCDFs), four non-ortho-polychlorinated biphenyls PCBs (nPCBs), and Toxic Equivalencies (TEQs) in a sample of residents in the most polluted zones A and B and in a reference non-contaminated zone. Methods: From December 1992 to March 1994, 62 individuals were randomly selected from the population living in zone A (No. =7) and B (No. =55). A sample of 59 subjects living in a surrounding non-contaminated area (non-ABR), frequency-matched by gender, age, and smoking history, was used as reference. All subjects were administered a questionnaire surveying demographic, lifestyle, medical history, and accident-related factors. We assayed plasma PCDD, PCDF, and nPCB concentrations by high-resolution gas chromatography/high resolution mass spectrometric (HRGC/HRMS) analysis, with results reported as pg/g of lipid, or parts per trillion (ppt). We calculated TEQs using the WHO 2005 Toxic Equivalency Factors (TEFs). Results: We found elevated median levels of 2,3,7,8-TCDD in plasma samples of subjects living in zone A (73.3 ppt) and zone B (12.4 ppt), compared with residents in the reference zone (5.5 ppt). In analyses adjusted for gender, age, smoking, and body mass index (BMI), none of the other congeners showed levels higher than reference in the contaminated zones. Compared with men, women showed higher levels (113%) of 2,3,7,8-TCDD and a slight elevation (17%) of TEQ for the other congeners. Age was strongly positively associated with most congener levels; TEQs for PCDDs, PCDFs, and nPCBs showed respectively 12%, 24%, and 41% increases for every 10 years of age. Current smokers had lower (from -37% to -67%) TEQ levels than subjects who had never smoked. BMI was negatively associated with levels of a few congeners, but with no impact on TEQ values. Conclusions: The Seveso accident caused a severe exposure of the population to 2,3,7,8-TCDD only. None of the other congeners analyzed showed variation across zones. Age showed a strong positive association with TEQs for all classes of compounds (PCDDs, PCDFs, and nPCBs).RiassuntoLivelli plasmatici di diossine, furani, non-orto-PCB e TEQ nella popolazione di Seveso 17 anni dopo l’incidenteIntroduzione: L’incidente Seveso del 1976 causò la contaminazione di una vasta popolazione dell’area con 2,3,7,8-tetraclorodibenzo-para-diossina (2,3,7,8-TCDD). Il territorio inquinato fu suddiviso in tre zone: A (contaminazione molto alta), B (alta contaminazione), R (bassa contaminazione). In questo articolo riportiamo le concentrazioni plasmatiche di 7 dibenzo-para-diossine policlorurate (PCDD), 10 dibenzofurani policlorurati (PCDF), 4 non-orto bifenili policlorurati (nPCB) ed Equivalenze Tossiche (TEQ) in un campione di residenti nelle zone più inquinate A e B e in una zona non inquinata di riferimento. Metodi: Fra il dicembre 1992 e il marzo 1994, 62 soggetti furono selezionati casualmente dalla popolazione residente in zona A (N. 7) e B (N. 55). Come riferimento fu usato un campione di 59 soggetti residenti in una zona circostante non inquinata (non-ABR), appaiato per genere, età e abitudini di fumo. Ai soggetti fu somministrato un questionario su caratteristiche demografiche, abitudini di vita, storia medica e fattori legati all’incidente. Tramite high-resolution gas chromatography/high resolution mass spectrometric (HRGC/HRMS) furono misurate le concentrazioni plasmatiche di PCDD, PCDF e nPCB, espresso in pg/g di lipidi, o parti per trilione (ppt). Le TEQ sono state calcolate  utilizzando i fattori di equivalenza tossica (TEF) stabiliti dall’OMS nel 2005. Risultati: Abbiamo riscontrato elevate livelli mediani di 2,3,7,8-TCDD nei campioni plasmatici dei soggetti di zona A (73,3 ppt) e zona B (12,4 ppt), in confronto ai residenti nella zona di riferimento (5,5 ppt). In analisi aggiustate per genere, età, fumo e indice di massa corporea (BMI), per nessuno degli altri congeneri le zone contaminate mostravano livelli più elevati del riferimento. In confronto agli uomini le donne mostravano livelli più elevati (113%) di 2,3,7,8-TCDD e una lieve aumento (17%) della TEQ per gli altri congeneri. L’età era fortemente positivamente associata coi livelli della  maggior parte dei congeneri; le TEQ per PCDD, PCDF, and nPCB mostravano aumenti rispettivamente del 12%, 24% e 41% per ogni decade di età. Gli attuali fumatori avevano livelli più bassi (da -37% a -67%) di TEQ rispetto ai mai fumatori. Il BMI era negativamente associato coi livelli di pochi congeneri, ma senza impatto sui valori di TEQ. Conclusioni: L’incidente di Seveso causò una severa esposizione della popolazione alla sola 2,3,7,8-TCDD. Nessuno degli altri congeneri ha mostrato variazioni tra zone. Per l’età si è evidenziata una forte associazione positiva con le TEQ di tutte le classi di composti (PCDD, PCDF, nPCB).